Natural Killer Anti-Tumor Activity Can Be Achieved by In Vitro Incubation With Heat-Killed BCG - Esteso, Gloria; Aguiló, Nacho; Julián, Esther; Ashiru, Omodele; Ho, Mei. M.; Martín, Carlos; Valés-Gómez, Mar (Frontiers in Immunology, 2021)
Natural Killer cell receptors allow this heterogeneous immune population to efficiently fight both tumors and infection, so their use as immunotherapy agents is an active field of research. Cytokine activation, particularly by myeloid cell-derived IL15, can induce potent NK anti-tumor responses. While studying the mechanism of action of intravesical instillations of Bacille Calmette-Guérin (BCG) as therapy for patients with high risk non-muscle invasive bladder cancer, we showed that BCG can activate a cytotoxic CD56bright NK cell population which efficiently recognized bladder cancer cells. This pioneer immunotherapy provides an invaluable model to understand the role of different immune populations in tumor elimination. However, during the propagation of BCG worldwide a large number of genetically diverse BCG substrains developed. Here, we investigated the capacity of different BCG substrains to promote NK cell activation and confirmed that they were able to activate lymphocytes. Tice, Connaught and Moreau were the substrains with a stronger NK activation effect as measured by CD56 upregulation. Surprisingly, dead mycobacteria also stimulated PBMC cultures and we further demonstrate here that subcellular fractions of BCG-Tice, in the absence of live mycobacteria, could also induce an NK cell response. Lipids from BCG-Tice, but not from Mycobacterium bovis, stimulated NK cell activation and degranulation, whereas the aqueous fraction of either bacteria did not activate lymphocytes. However, delipidated BCG-Tice bacteria were able to activate effector cells (CD3+CD56+ and NK, CD3-CD56+). These data demonstrate that different components of mycobacteria can stimulate different immune subpopulations resulting in phenotypes suitable for cancer elimination.